Hubungan Dukungan Keluarga terhadap Tingkat Kemandirian Activity Daily Living di pada Pasien Skizorenia di Rumah Sakit Umum Daerah Embung Fatimah Kota Batam - Lis Kartika Sari; Isna Aguslu Badri (Jurnal Siti Rufaidah, 2025)
According to data from the World Health Organization (WHO), approximately 24 million people worldwide, or about one in every 300 individuals, live with schizophrenia. Individuals with schizophrenia commonly experience reduced independence in performing daily functions and social roles, including self-care, employment, and social interaction. This decline in independence is closely related to disturbances in thought processes, which subsequently affect their ability to carry out activities of daily living (ADL). This study aimed to examine the relationship between family support and the level of ADL independence among patients with schizophrenia at Embung Fatimah Hospital, Batam City, in 2024. The research employed an analytical correlation approach with a cross-sectional design and involved 60 families who lived in the same household as schizophrenia patients. Data collection was conducted from October 1 to October 9, 2024, using a purposive sampling technique and structured questionnaires. The findings revealed that the majority of respondents perceived family support as adequate, accounting for 38 respondents (63.3%), while 29 patients (48.3%) demonstrated a sufficient level of ADL independence. Bivariate analysis using the Spearman rank correlation test showed a correlation coefficient of r = 0.605 with a p-value of 0.000 (< 0.05), indicating a statistically significant relationship between family support and ADL independence. These results confirm that stronger family support is associated with higher levels of independence in daily activities among schizophrenia patients. Therefore, families are encouraged to consistently provide emotional, instrumental, and motivational support to help patients maintain and improve their daily functioning.